A diverse suite of pharmaceuticals contaminates stream and riparian food webs. Issue 1 (December 2018) - Richmond, Erinn; Rosi, Emma; Walters, David; Fick, Jerker; Hamilton, Stephen; Brodin, Tomas; Sundelin, Anna; Grace, Michael
Abstract A multitude of biologically active pharmaceuticals contaminate surface waters globally, yet their presence in aquatic food webs remain largely unknown. Here, we show that over 60 pharmaceutical compounds can be detected in aquatic invertebrates and riparian spiders in six streams near Melbourne, Australia. Similar concentrations in aquatic invertebrate larvae and riparian predators suggest direct trophic transfer via emerging adult insects to riparian predators that consume them. As representative vertebrate predators feeding on aquatic invertebrates, platypus and brown trout could consume some drug classes such as antidepressants at as much as one-half of a recommended therapeutic dose for humans based on their estimated prey consumption rates, yet the consequences for fish and wildlife of this chronic exposure are unknown. Overall, this work highlights the potential exposure of aquatic and riparian biota to a diverse array of pharmaceuticals, resulting in exposures to some drugs that are comparable to human dosages. Pharmaceuticals are widespread contaminants in surface waters. Here, Richmond and colleagues show that dozens of pharmaceuticals accumulate in food chains of streams, including in predators in adjacent terrestrial ecosystems.